2012
DOI: 10.1080/00222895.2012.684909
|View full text |Cite
|
Sign up to set email alerts
|

Unimanual and Bimanual Continuous Movements Benefit From Visual Instructions in Persons With Down Syndrome

Abstract: The authors' aim was to understand how persons with Down syndrome (DS) perform different tasks and to assess if there were any differences in performance based on the type of instructions. This is important because of neurological differences in persons with DS and neurological demands for performing different types of tasks. Twenty right-handed participants with DS, 20 chronological age-matched (CA), and 20 mental age-matched (MA) performed unimanual, bimanual, discrete, and continuous drumming following visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Post-hoc comparisons showed that children with ASD threw more accurately after a visual analogy [ 79 ]. Similar results were found in studies with healthy young adults and young adults with Down syndrome, where skill performance improved more after video [ 94 , 95 ] or instructor demonstration [ 96 ] than with verbal instructions with EF. Although evidence is limited, instructors might consider using pictures, videos or real live demonstrations as instructions or feedback to teach children motor skills.…”
Section: Discussionsupporting
confidence: 84%
“…Post-hoc comparisons showed that children with ASD threw more accurately after a visual analogy [ 79 ]. Similar results were found in studies with healthy young adults and young adults with Down syndrome, where skill performance improved more after video [ 94 , 95 ] or instructor demonstration [ 96 ] than with verbal instructions with EF. Although evidence is limited, instructors might consider using pictures, videos or real live demonstrations as instructions or feedback to teach children motor skills.…”
Section: Discussionsupporting
confidence: 84%
“…Post-hoc comparisons showed that children with ASD threw more accurately after a visual analogy (83). Similar results were found in studies with healthy young adults and young adults with Down syndrome, where skill performance improved more after video (88,89) or instructor demonstration (90) than with verbal instructions with EF. Although evidence is limited, instructors might consider using pictures, videos or real live demonstrations as instructions or feedback to teach children motor skills.…”
Section: Discussionsupporting
confidence: 85%
“…EPG has minimal cognitive and language demands and also capitalizes on the known relative strength of visual versus auditory processing ability in children with DS (e.g., Fidler and Nadel , Ringenbach et al . ). Weismer et al .’s () suggestion that tongue control is strongly related to speech intelligibility further strengthens the argument for exploring the utility of a VBF technique to target lingual errors in children with DS.…”
Section: Introduction: Backgroundmentioning
confidence: 97%